Internship Challenges Encountered by Nursing Students: A Qualitative Study Conducted at the Highest Institutions in Ethiopia - Nigussie Bolado G; Atinafu Ataro B; Agana A; Elfios Endirias E; Haile KE; Addisie A; Mulatu G; Geta T; Toru T; Kebede C (Nursing: Research and Reviews, 2023)
Getachew Nigussie Bolado,1 Bizuayehu Atinafu Ataro,1 Ayele Agana,1 Eshetu Elfios Endirias,1 Kirubel Eshetu Haile,1 Almaz Addisie,2 Gebremeskel Mulatu,3 Temesgen Geta,4 Tigistu Toru,4 Christian Kebede5 1Department of Nursing, School of Nursing, College of Health Science and Medicine, Wolaita Sodo University, Sodo, Ethiopia; 2Department of Adult Health Nursing, School of Nursing and Midwifery, Addis Ababa University, Addis Ababa, Ethiopia; 3Department of Nursing, School of Nursing and Midwifery, Mettu University, Mettu, Ethiopia; 4Maternity and Reproductive Health in Nursing, School of Nursing, College of Health Science and Medicine, Wolaita Sodo University, Sodo, Ethiopia; 5Pediatrics Nursing, School of Nursing, College of Health Science and Medicine, Wolaita Sodo University, Sodo, EthiopiaCorrespondence: Getachew Nigussie Bolado, Email getachewnigussie4@gmail.comBackground: The clinical learning environment is important for achieving defined learning outcomes in nursing education programs; however, nursing students reportedly fail to accomplish the intended objectives of skill development and are not sufficiently competent. Although several studies have attempted to determine the magnitude of skill incompetence, these challenges have not been explored thoroughly.Objective: To explore the challenges experienced by nursing students during their internship at the highest institutions in Addis Ababa, Ethiopia.Methods: This phenomenological study was conducted with seven purposively selected nursing student participants to explore the challenges. Data were collected using a semi-structured interview guide with open-ended questions; telephone interviews were done, and notes were organized from May to July 2022. Content thematic analysis were done using the seven-step approach of Colaizzi’s framework of analysis.Results: Five themes were identified, namely: nursing students’ factors; role model-related factors; factors related to instructors; factors related to the responsibilities of the institutions; and factors related to time constraints were among the challenges experienced by nursing students. Participants raised that low motivation and willingness to learn among nursing students, lack of support and guidance, large number of students per clinical attachment, improper assessment methods, lack of learning equipment, lack of sufficient time for simulations (skill laboratory demonstration), and poor time management for theory and practice activities were some of the specific challenges they faced during their clinical internships.Conclusion: The challenges nursing students at the highest institutions encountered during their internship were factors related to nursing students; role model-related factors; factors related to instructors; factors related to the responsibilities of the institutions; and factors related to time constraints. Therefore, effective communication and understanding among concerned bodies are needed to better reflect these challenges, and an appropriate plan and intervention should be done to improve students’ clinical supervision and support.Keywords: internship challenges, highest institutions, nursing students, Ethiopia